The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/suco.201800057
|View full text |Cite
|
Sign up to set email alerts
|

Recycling fresh concrete waste: A review

Abstract: Disposal of fresh concrete waste is a worldwide problem. In recent years, many studies have claimed that fresh concrete waste from a reclaiming system can be efficiently recycled into concrete. This paper gives a comprehensive review of the characteristics and applicability of fresh concrete waste in phase of slurry wastewater, fresh paste, and recycled solids. The effects of fresh concrete waste in the three phases on workability, strength, and durability such as permeability, water absorption, shrinkage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
(182 reference statements)
0
16
0
1
Order By: Relevance
“…In recent years, a trend has been emerged to use concrete waste instead of natural resources in the production of concrete with the increase in consumption . The research results showed that the mechanical properties of recycled aggregate concrete (RAC) are generally lower than that of normal concrete (NC), but they are still sufficient for some practical applications in Civil Engineering …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a trend has been emerged to use concrete waste instead of natural resources in the production of concrete with the increase in consumption . The research results showed that the mechanical properties of recycled aggregate concrete (RAC) are generally lower than that of normal concrete (NC), but they are still sufficient for some practical applications in Civil Engineering …”
Section: Introductionmentioning
confidence: 99%
“…This recycled aggregate was used in concrete, with up to 30% replacement of the natural aggregates. However, this technique is significantly different from the other fresh concrete waste recycling techniques commonly reported in the literature [40][41][42].…”
Section: Introductionmentioning
confidence: 85%
“…Marco [13] found that the compressive strength of concrete mixed with waste slurry is slightly lower than that of concrete without waste slurry. Li, Xiao and others provided even more experimental results [14][15][16][17][18][19].…”
Section: Effects Of Waste Slurry On Mechanical Propertiesmentioning
confidence: 99%
“…The waste slurry is strongly alkaline, which gives play to the later activity of slag powder and produces stable hydration products. Many scholars [18][19][20][21] held that the concrete mixed with waste slurry is stronger than that mixed with tap water.…”
Section: Effects Of Waste Slurry On Microstructurementioning
confidence: 99%